The Handbook of equipment leasing - Amembal, Sudhir P. (Utah: Amembal y Halladay, 1989)
Este texto cntiene los siguientes capitulos: Overview of the industry,evolution leasing,dinamycs of the industry,IRS qualifications of a lease.income tax considerations,lease versus buy,lease analysis,structuring principles,advance structuring,capital budgeting and financial management
Keywords: Abastecimiento; Administración de Materiales